2019
DOI: 10.1371/journal.pone.0225737
|View full text |Cite
|
Sign up to set email alerts
|

Improved oxygenation following methylprednisolone therapy and survival in paediatric acute respiratory distress syndrome

Abstract: BackgroundMethylprednisolone remains a commonly used ancillary therapy for paediatric acute respiratory distress syndrome (PARDS), despite a lack of level 1 evidence to justify its use. When planning prospective trials it is useful to define response to therapy and to identify if there is differential response in certain patients, i.e. existence of ‘responders’ and ‘non responders’ to therapy. This retrospective, observational study carried out in 2 tertiary referral paediatric intensive care units aims to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, those that received steroids were less likely to require supplemental oxygen at transfer out of the PICU. Finally, another observational study also suggests that children with PARDS who have an improvement in oxygenation following steroid administration have greater odds of survival (74% vs 41%; OR, 4.14; 95% CI, 1.57–10.87; p = 0.004) (56).…”
Section: Resultsmentioning
confidence: 99%
“…However, those that received steroids were less likely to require supplemental oxygen at transfer out of the PICU. Finally, another observational study also suggests that children with PARDS who have an improvement in oxygenation following steroid administration have greater odds of survival (74% vs 41%; OR, 4.14; 95% CI, 1.57–10.87; p = 0.004) (56).…”
Section: Resultsmentioning
confidence: 99%
“… 12 Improvement of oxygenation within 1 to 2 days of corticosteroids therapy has been proved to be correlated with reduced ICU mortality in pediatric patients with ARDS. 13 On the other hand, side effects like secondary infections may take weeks to occur, 14 which imply that it is possible and crucial to predict the prognosis of corticosteroid-treated patients based on their early response to the drug. Besides, timely withdrawn of the corticosteroids for non-responsive patients may avoid side effects of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…55 1.2 Steroid treatment improves oxygen saturation index in patents. The study performed by Mitting et al 56 on a cohort of 78 PARDS patients who had received methylprednisolone over 5 years (2011-2016) showed a >20% increase in oxygen saturation index in 60% of the patients. Regarding steroid treatment, 59% of the patients showed a response.…”
mentioning
confidence: 98%
“…However, more prospective studies are necessary to ascertain the effectiveness of the steroid therapy. 56 1.3 Steroid treatment reduces levels of inflammatory cytokines. De Luca et al 57 revealed a connection between high inflammatory cytokine levels and ARDS in infant bronchoalveolar lavage fluid.…”
mentioning
confidence: 99%